Elementos del Discurso del Profesor que Favorezcan el Aprendizaje en las Aulas Universitarias - Morales Hidalgo, Paulina De los Angeles (2018)
The communication processes in the university classrooms are of vital importance, the discourse of the teacher, with its didactic doing, favors or not the learning of the adult as a series of codes intervene that are not limited to the linguistic ones, besides the object of study to be decoded This originates the investigation and semiotic analysis of this discourse to describe the elements that intervene there, it is a qualitative research, with a criticalsocio-paradigm with a Dialectical Hermeneutical method. The results of the researchidentified the different components that the adult learners face in the communicative processes of the classroom, which served as an input to describe the elements of the teacher's discourse using semiotics as a fundamental instrument of interpretation and decoding of the different codes sociolinguísticos.es a research, with an experiential introspective approach, which is not static represents a fully dynamic and changing ontological reality.